MEGAPORELLA NIKLERI N. SP., A NEW CALCAREOUS ALGA (DASYCLADALES) FROM THE UPPER BARREMIAN OF MT. BIOKOVO, CROATIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The genus Megaporella Deloffre & Beun, 1986, is emended, and a new species, Megaporella nikleri n. sp., is established. The species is characterized by vesiculiferous and sporadically phloiophorous branches, arranged in whorls. Their number per whorl is variable and their distribution in consecutive whorls is unequal, giving a picture of a seemingly aspondyl arrangement in tangential section. The new species occurs in Upper Barremian.